Wet catalytic oxidation treatment method for high-salinity wastewater

By using wet catalytic oxidation treatment method and RuO-CuO-Fe2O3-TiO2 catalyst in the glycerol epoxy production process, the problem of high-salt and high-COD wastewater treatment is solved, and the wastewater treatment effect with low cost and low energy consumption is achieved.

CN119797563APending Publication Date: 2025-04-11武媛媛
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510054545.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively treat the high-salt and high-COD wastewater generated in the production process of glycerol epoxy chlorohydrin under low cost and low energy consumption.

Method used

Wet catalytic oxidation treatment method is adopted, and wastewater is treated under mild conditions using RuO-CuO-Fe2O3-TiO2 catalyst, and gas-liquid turbulent mixing is achieved through the bedroom reactor, reducing the cost of wastewater treatment.

Benefits of technology

The low-cost treatment of high-salt and high-COD wastewater is achieved, the wastewater treatment cost is reduced, and the treatment effect reaches the emission standards, and the COD can be reduced to below 100 ppm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797563A_ABST
    Figure CN119797563A_ABST
Patent Text Reader

Abstract

The invention relates to a wet catalytic oxidation treatment method for high-salinity wastewater. The reactor is a bedroom reactor and is filled with a catalytic oxidation catalyst, gas enters from the bottom of the reactor, liquid enters from the two sides of the reactor, gas-liquid turbulent mixing is achieved, and the wastewater treatment effect is greatly improved. The composition of the catalyst is a RuO-CuO-Fe2O3-TiO2 system, and the CuO-Fe2O3-TiO2 system is The catalyst carrier adopts metatitanic acid generated in the hydrolysis process of titanium dioxide, the metatitanic acid is filtered, dried and ground to obtain a solid, and water is further added for extrusion molding to obtain the titanium oxide carrier. And the catalytic wet oxidation catalyst is obtained through multiple times of equivalent-volume impregnation. According to the total weight of the catalyst, the RuO-CuO-Fe2O3-TiO2 catalyst is prepared from the following components in percentage by weight: 1 to 5 percent of ruthenium oxide, 10 to 20 percent of copper oxide, 2 to 10 percent of iron oxide and 60 to 85 percent of titanium oxide. The highest COD (Chemical Oxygen Demand) receivable range in the wastewater is 1000-30000 ppm, and the COD can be reduced to 100 ppm or below after the wastewater is treated, so that the wastewater reaches the discharge standard.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wastewater treatment technology and catalysts thereof, and specifically relates to a wet catalytic oxidation treatment method for high-salt concentration wastewater. Background Art

[0002] In the prior art, epichlorohydrin (ECH) is mainly used to produce epoxy resins, glycerol, epichlorohydrin rubber and other derivatives. It can also be used as a solvent, plasticizer, flame retardant and surfactant. It is an important organic chemical raw material and an important intermediate in petrochemicals and has a wide range of uses.

[0003] At present, the production processes of epichlorohydrin include chlorination method, glycerol method and direct oxidation method with hydrogen peroxide. The glycerol method is currently the mainstream process in the market due to its lower cost.

[0004] Chinese patent document CN201910597743.4 discloses a technology for treating high-salt epichlorohydrin wastewater. The process uses a pretreatment + catalytic oxidation scheme to treat high-salt wastewater, with a calcium chloride concentration of 10-35%, a TOC content of 2000-12000 mg / L, and a pH value of 8-12. The pretreated wastewater is oxidized with oxygen-containing gas at a temperature of 160-280°C and a pressure of 1.2-7.5 MPa for 1-4 hours. After the wastewater is treated, the TOC is reduced to 20 mg / L, which meets the emission standards. The scheme described in this aspect can effectively treat high-salt wastewater, but the reaction temperature and pressure conditions are both high, and the cost of wastewater treatment is high.

[0005] Chinese patent document CN202010681385.8 introduces a process for treating epichlorohydrin saponification wastewater, which separates organic matter and salt CaCl2 in saponification wastewater by electrodialysis, concentrates CaCl2 at the same time, and then adds NaOH liquid to the high-concentration CaCl2 liquid to produce Ca(OH)2, thereby realizing the recycling of Ca(OH)2; the supernatant in the sedimentation tank is treated by ultrafiltration and resin tank, and then the bipolar membrane system is used to prepare NaOH liquid and dilute hydrochloric acid, thereby realizing the recycling of NaOH, and dilute hydrochloric acid is used as a by-product. The patent only introduces the operation process of the process, and the operation effect is not listed in detail.

[0006] As can be seen from the prior art described above, the prior art has many defects, and it is still very necessary to explore a low-cost, low-energy consumption, organic pollutant mineralization treatment method for high-salt organic wastewater containing calcium chloride generated in the production process of epichlorohydrin by the glycerol method. The present invention creatively combines the reaction process and the catalyst to treat high-salt, high-COD wastewater under milder conditions, thereby realizing the development of a low-cost treatment solution for high-salt wastewater. Summary of the invention

[0007] The purpose of the present invention is to provide a method for treating wastewater with high salt concentration by wet catalytic oxidation. In view of the application scenario where high-salt wastewater treatment is difficult, the treatment of high-salt and high-COD wastewater is difficult, and conventional biological methods cannot be applied to high-salt wastewater. The present invention adopts a wet catalytic oxidation process for treatment. The reactor is a bedroom reactor with a catalytic oxidation catalyst installed. The gas enters from the bottom of the reactor and the liquid enters from both sides of the reactor to achieve turbulent mixing of gas and liquid, greatly increasing the wastewater treatment effect.

[0008] To achieve the above object, the technical solution adopted by the present invention is: A method for treating wastewater with high salt concentration by wet catalytic oxidation, which uses a catalyst that can tolerate high salt concentration to treat the wastewater by catalytic wet oxidation, wherein the catalyst is placed in a reactor, and gas and liquid are fed separately, with the gas entering from the bottom of the reactor and the liquid entering from the side of the reactor, and the two phases are mixed together to achieve dispersion; the catalyst is composed of a RuO-CuO-Fe2O3-TiO2 catalyst, which includes 1-5 wt% of ruthenium oxide, 10-20 wt% of copper oxide, 2-10 wt% of iron oxide, and 65-80 wt% of titanium oxide, based on the total weight of the catalyst.

[0009] The above scheme also includes: The reaction pressure in the reactor is 2-4 MPa, the reaction temperature is 80-150 °C, the wastewater treatment capacity is 0.5-2 g / gcat.h, and the air gas velocity is 1500-2500 h -1 .

[0010] The catalyst is preferably 2-4 wt% ruthenium oxide, 12-18 wt% copper oxide, 4-8 wt% iron oxide, and 70-80 wt% titanium oxide.

[0011] The catalyst preparation method is as follows: (1) Take the titanic acid produced by hydrolysis in the titanium dioxide industry, filter it, dry it at 80-120℃, and grind it into powder less than 150μm.

[0012] (2) The powder is mixed evenly with sesbania powder and hydroxymethyl cellulose, wherein the sesbania powder accounts for 3-8 wt% of the powder mass and the hydroxymethyl cellulose accounts for 1-5 wt% of the powder mass. The mixed powder and water are kneaded in a ratio of 100:60-80 to form a wet embryo, which is then extruded using a 2 mm cloverleaf mold, dried at 80-120 °C and calcined at 400-600 °C to obtain a titanium oxide carrier.

[0013] (3) Test the water absorption rate of the carrier. According to the water absorption rate, prepare copper nitrate trihydrate and ferric nitrate nonahydrate (nitrate becomes copper oxide and ferric oxide after calcination. Nitrate can be considered as a precursor. After calcination, the iron and copper in the catalyst exist in the form of copper oxide and ferric oxide) into a saturated concentration solution. Mix the saturated solution with the carrier for adsorption at room temperature. After saturation, let it stand for 1-2 hours. Then, dry it in a rotary vacuum drying equipment and calcine it to obtain a catalyst precursor.

[0014] (4) According to the saturated water absorption rate of the precursor, ruthenium trichloride (ruthenium trichloride is equivalent to nitrate, and after calcination, it is in the form of ruthenium oxide in the catalyst) is prepared into a saturated solution, and the saturated solution is mixed with the carrier for adsorption at room temperature. After saturated adsorption, it is allowed to stand for 1-2 hours, and then dried and calcined in a rotary vacuum drying equipment to obtain a catalyst.

[0015] The advantages of the present invention are: (1) Gas and liquid are fed in different directions and dispersed together through two-phase flow mixing.

[0016] (2) The high-salt wastewater treatment method described in the present invention has higher tolerance to salt concentration and COD, and the reaction conditions are milder, which can significantly reduce the cost of wastewater treatment.

[0017] (3) The catalyst described in the present invention has higher catalytic oxidation activity, making it possible to decompose high-salt, high-COD wastewater at low temperature and low pressure, and matching the reaction process to improve the overall wastewater treatment effect. The maximum acceptable COD range in wastewater is 1000-30000 ppm. After wastewater treatment, COD can be reduced to below 100 ppm, meeting the discharge standard.

[0018] The method of the present invention is described in detail below with reference to the embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Schematic diagram of the reactor of the present invention. DETAILED DESCRIPTION

[0020] See also Figure 1 The names of the parts are as follows: air 1, wastewater inlet pipe 2, catalyst 3, reactor 4. Example 1

[0021] Catalyst preparation: Take the titanic acid produced by hydrolysis of titanium dioxide (TiO2) industry, filter it, dry it at 120℃, and grind it into powder of less than 150 μm.

[0022] TiO2 powder is evenly mixed with sesbania powder and hydroxymethyl cellulose, the amount of sesbania powder added is 5wt% of TiO2, and the amount of hydroxymethyl cellulose added is 3wt% of TiO2. The mixed powder and water are kneaded in a ratio of 100:60 to form a wet embryo, which is then extruded using a 2 mm cloverleaf mold, and then dried at 120°C and calcined at 600°C to obtain a titanium oxide carrier.

[0023] Take 79 g of the calcined titanium oxide carrier, dissolve 30.2 g of copper nitrate trihydrate and 30.3 g of ferric nitrate nonahydrate in 63.2 g of water at room temperature, pour the salt solution into the carrier for impregnation liquid adsorption, let it stand for 2 h after saturated adsorption, then dry it at 60 ° C and 5 kPaA vacuum for 3 h in a rotary vacuum drying equipment, and then calcine at 400 ° C for 3 h to obtain a catalyst precursor.

[0024] 7.79 g of ruthenium trichloride was dissolved in 63.2 g of water. After dissolution, the salt solution was poured into the carrier for impregnation liquid adsorption. After saturated adsorption, it was allowed to stand for 2 h. Subsequently, it was dried at 60 °C and 5 kPaA vacuum for 2 h in a rotary vacuum drying equipment and calcined at 500 °C for 2 h to obtain the catalyst.

[0025] The catalyst is placed in the reactor, air enters from the bottom of the reactor, and wastewater enters from both sides of the reactor to achieve turbulent mixing of gas and liquid. The catalyst loading is 100 g, the reaction pressure is 2 MPa, the reaction temperature is 150 °C, the wastewater treatment capacity is 2 g / gcat.h, and the air intake space velocity is 2500 h -1 , sodium process epichlorohydrin wastewater feed, sodium chloride concentration is 3%, COD is 15000 ppm, after treatment it is 26 ppm. Example 2

[0026] Catalyst preparation: Take the titanic acid produced by hydrolysis in the titanium dioxide industry, filter it, dry it at 120°C, and grind it into powder of less than 150 μm.

[0027] TiO2 powder was evenly mixed with sesbania powder and hydroxymethyl cellulose, with the sesbania powder added in an amount of 5wt% of TiO2 and the hydroxymethyl cellulose added in an amount of 3wt% of TiO2. The mixed powder and water were kneaded in a ratio of 100:60 to form a wet embryo, which was then extruded using a 2 mm cloverleaf mold, and then dried at 100°C and calcined at 550°C to obtain a titanium oxide carrier.

[0028] Take 79 g of the calcined titanium oxide carrier, dissolve 45.3 g of copper nitrate trihydrate and 15.15 g of ferric nitrate nonahydrate in 63.2 g of water at room temperature, pour the salt solution into the carrier for impregnation liquid adsorption, let it stand for 2 hours after saturated adsorption, then dry it at 65 ° C and 15 kPaA (absolute pressure) in a rotary vacuum drying equipment for 4 hours, and calcine it at 400 ° C for 3 hours to obtain a catalyst precursor.

[0029] 4.68 g of ruthenium trichloride was dissolved in 63.2 g of water. After dissolution, the salt solution was poured into the carrier for impregnation liquid adsorption. After saturated adsorption, it was allowed to stand for 2 h. Subsequently, it was dried at 60 °C and 5 kPa (absolute pressure) in a rotary vacuum drying equipment for 3 h, and calcined at 500 °C for 2 h to obtain the catalyst.

[0030] The catalyst is placed in the reactor, air enters from the bottom of the reactor, and wastewater enters from both sides of the reactor to achieve turbulent mixing of gas and liquid. The catalyst loading is 100 g, the reaction pressure is 3 Mpa, the reaction temperature is 110 ℃, the wastewater treatment capacity is 1.25 g / gcat.h, and the air intake space velocity is 2000 h -1 , sodium process epichlorohydrin wastewater feed, sodium chloride concentration is 3%, COD is 15000 ppm, and after treatment it is 30 ppm. Example 3

[0031] Catalyst preparation: Take the titanic acid produced by hydrolysis in the titanium dioxide industry, filter it, dry it at 100 °C, and grind it into powder of less than 150 μm.

[0032] TiO2 powder was evenly mixed with sesbania powder and hydroxymethyl cellulose, with the sesbania powder added in an amount of 5wt% of TiO2 and the hydroxymethyl cellulose added in an amount of 3wt% of TiO2. The mixed powder and water were kneaded in a ratio of 100:60 to form a wet embryo, which was then extruded using a 2 mm cloverleaf mold, and then dried at 100°C and calcined at 550°C to obtain a titanium oxide carrier.

[0033] Take 71 g of the calcined titanium oxide carrier, dissolve 60.4 g of copper nitrate trihydrate and 40.4 g of ferric nitrate nonahydrate in 56.8 g of water at room temperature, pour the salt solution into the carrier for impregnation liquid adsorption, let it stand for 2 h after saturated adsorption, then dry it at 60 ° C and 10 kPaA (absolute pressure) for 3.5 h in a rotary vacuum drying equipment, and calcine it at 400 ° C for 3 h to obtain a catalyst precursor.

[0034] 1.56 g of ruthenium trichloride was dissolved in 56.8 g of water. After dissolution, the salt solution was poured into the carrier for impregnation liquid adsorption. After saturated adsorption, it was allowed to stand for 2 h. It was then dried at 60 °C and 5 kPaA (absolute pressure) for 3 h in a rotary vacuum drying equipment and calcined at 500 °C for 3 h to obtain the catalyst.

[0035] The catalyst is placed in the reactor, air enters from the bottom of the reactor, and wastewater enters from both sides of the reactor to achieve turbulent mixing of gas and liquid. The catalyst loading is 100 g, the reaction pressure is 4 MPa, the reaction temperature is 80 °C, the wastewater treatment capacity is 0.5 g / gcat.h, and the air intake space velocity is 1500 h -1 , sodium process epichlorohydrin wastewater feed, sodium chloride concentration is 3%, COD is 15000 ppm, and after treatment it is 18 ppm.

[0036] The maximum acceptable range of COD in wastewater is 1000-30000 ppm. After wastewater treatment, COD can be reduced to below 100 ppm, meeting the discharge standards.

[0037] Commercially available 5% RuO-Al2O3 wet catalytic oxidation catalyst.

[0038] The catalyst is placed in the reactor, and the wastewater and air are mixed at the reactor inlet, using the top-in and bottom-out operation mode. The catalyst loading is 100 g, the reaction pressure is 4 Mpa, the reaction temperature is 80 ℃, the wastewater treatment capacity is 0.5 g / gcat.h, and the air inlet velocity is 1500 h -1 , sodium process epichlorohydrin wastewater feed, sodium chloride concentration is 3%, COD is 15000 ppm, and after treatment it is 2500 ppm.

[0039] Take the titanic acid produced by hydrolysis in the titanium dioxide industry, filter it, dry it at 100 °C, and grind it into powder of less than 150 μm.

[0040] TiO2 powder was mixed evenly with sesbania powder and hydroxymethyl cellulose, and the mixed powder and water were kneaded in a ratio of 100:60 to form a wet embryo, which was then extruded using a 2 mm cloverleaf mold, and then dried at 100 °C and calcined at 550 °C to obtain a titanium oxide carrier.

[0041] Take 85 g of the calcined titanium oxide carrier, dissolve 50.5 g of ferric nitrate nonahydrate in 68 g of water at room temperature (Comparative Example 2 does not contain copper element), pour the salt solution into the carrier for impregnation liquid adsorption after dissolution, let it stand for 2 hours after saturation, and then obtain the catalyst precursor in a rotary vacuum drying equipment at 60 ° C and 10 kPaA (absolute pressure).

[0042] 7.79 g of ruthenium trichloride was dissolved in 68 g of water. After dissolution, the salt solution was poured into the carrier for impregnation liquid adsorption. After adsorption saturation, it was allowed to stand for 2 h, and then the catalyst was obtained in a rotary vacuum drying equipment at 60 ° C and 5 kPaA (absolute pressure).

[0043] The catalyst is placed in the reactor, the gas enters from the bottom of the reactor, and the liquid enters from both sides of the reactor to achieve turbulent mixing of gas and liquid. The catalyst loading is 100 g, the reaction pressure is 4 MPa, the reaction temperature is 80 °C, the wastewater treatment capacity is 0.5 g / gcat.h, and the air intake space velocity is 1500 h -1 , sodium process epichlorohydrin wastewater feed, sodium chloride concentration is 3%, COD is 15000 ppm, and after treatment it is 950 ppm.

[0044] The above description is only a specific implementation mode of the present invention, and various examples do not constitute a limitation on the essential content of the present invention.

Claims

1. A method for treating high-salt concentration wastewater by wet catalytic oxidation, characterized in that A catalyst that can tolerate high salt concentration is used to carry out catalytic wet oxidation treatment of wastewater. The catalyst is placed in a reactor, and gas and liquid are fed separately, with the gas entering from the bottom of the reactor and the liquid entering from the side of the reactor, and dispersion is achieved through two-phase flow mixing. The catalyst is composed of a RuO-CuO-Fe2O3-TiO2 catalyst, which includes 1-5 wt% of ruthenium oxide, 10-20 wt% of copper oxide, 2-10 wt% of ferric oxide, and 65-80 wt% of titanium dioxide, based on the total weight of the catalyst.

2. A method for treating high-salt concentration wastewater by wet catalytic oxidation according to claim 1, characterized in that The reaction pressure in the reactor is 2-4 MPa, the reaction temperature is 80-150 °C, the wastewater treatment capacity is 0.5-2 g / gcat.h, and the air gas velocity is 1500-2500 h -1 .

3. A method for treating high-salt concentration wastewater by wet catalytic oxidation according to claim 1 or 2, characterized in that The catalyst is preferably 2-4 wt% of ruthenium oxide, 12-18 wt% of copper oxide, 4-8 wt% of iron oxide, and 70-80 wt% of titanium dioxide.

4. A method for treating high-salt concentration wastewater by wet catalytic oxidation according to claim 3, characterized in that The catalyst preparation method is as follows: (1) Take the titanic acid produced by hydrolysis in the titanium dioxide industry, filter it, dry it at 80-120℃, and grind it into powder less than 150μm; (2) The powder is uniformly mixed with sesbania powder and hydroxymethyl cellulose, wherein the sesbania powder accounts for 3-8 wt% of the powder mass and the hydroxymethyl cellulose accounts for 1-5 wt% of the powder mass, and the mixed powder and water are kneaded in a ratio of 100:60-80 to form a wet embryo, which is then extruded using a 2 mm clover leaf mold, dried at 80-120 ° C, and calcined at 400-600 ° C to obtain a titanium oxide carrier; (3) Testing the water absorption rate of the carrier, preparing copper nitrate trihydrate and ferric nitrate nonahydrate into a saturated concentration solution according to the water absorption rate, mixing the saturated solution with the carrier for adsorption at room temperature, standing for 1-2 hours after saturation, and then drying and calcining in a rotary vacuum drying device to obtain a catalyst precursor; (4) According to the saturated water absorption rate of the precursor, ruthenium trichloride is prepared into a saturated solution, and the saturated solution is mixed with the carrier for adsorption at room temperature. After saturated adsorption, it is allowed to stand for 1-2 hours, and then dried and calcined in a rotary vacuum drying equipment to obtain a catalyst.

Citation Information

Patent Citations

  • Ti-based fine desulfurization catalyst, as well as preparation method and use method thereof

    CN103272610A

  • Treatment method of high-salt organic wastewater generated in glycerol epoxy chloropropane production process

    CN110255772A

  • Pretreatment process for tobacco sheet wastewater

    CN110627256A

  • Hydrogenation catalyst and preparation method thereof, and application of hydrogenation catalyst in olefin removal of reformed C5 oil

    CN113398907A

  • Suspended bed catalytic ozonation reactor

    CN209922986U